PENETAPAN TARIF TRANSAKSI OLEH AGEN BRILINK DI KECAMATAN MEMPAWAH HULU MENURUT HUKUM EKONOMI SYARIAH (HES) - Azizah, Hergi Novfitrianingsih; Ma'u, Dahlia Haliah; Rahmiani, Nur (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
The focus of this research is to find out how BRILink Agents set BRILink transaction rates in Mempawah Hulu District and the implementation of setting transaction rates by BRILink Agents according to Sharia Economic Law. Researchers use qualitative methods that are qualitative perspectives, with the type of research type of field research, normative-empirical research approach. This research was conducted at the BRILink Agent of Mempawah Hulu District, Karangan Village, Landak Regency. The data sources of this research are BRI, BRILink agents and BRILink customers. The data collection techniques used are interviews, observation, and documentation. While the data analysis techniques used are data reduction, data presentation, conclusion drawing and verification. The results showed that: 1) Determination of service rates on BRILink agents has been determined by Bank BRI, but there are differences in tariff implementation among BRILink agents due to operational cost factors that affect administrative costs; 2) From the perspective of Sharia Economic Law, the determination of service rates between Bank BRI and BRILink Agents is considered valid because it is in accordance with the mudharabah principle which emphasizes the fair distribution of profits and losses. Tariff setting between banks and agents uses a mudharabah contract with a profit ratio of 50:50. The agreement between BRILink customers and BRILink agents is also considered valid by using the ijarah method in accordance with the concept of its pillars and conditions. The determination of additional transaction rates by BRILink agents is caused by operational costs that affect administrative costs, and these costs are included in the costs informed to customers.